Porphyromonas gingivalis outer membrane vesicles exacerbate retinal microvascular endothelial cell dysfunction in diabetic retinopathy - Huang, Shengyuan; Cao, Guoqin; Dai, Dong; Xu, Qiuping; Ruiz, Sunniva; Shindo, Satoru; Nakamura, Shin; Kawai, Toshihisa; Lin, Jiang; Han, Xiaozhe (Frontiers in Microbiology, 2023)
Diabetic retinopathy (DR) is one of the leading causes of blindness. Periodontitis is one of the highest oral incidences and has been closely related to various systemic conditions through Porphyromonas gingivalis (P. gingivalis). P. gingivalis OMVs, derived from P. gingivalis, can cause endothelial dysfunction and potentially affect microvascular diseases. Current epidemiological studies provide limited evidence suggesting that periodontitis is associated with DR. However, there is a lack of basic research elucidating how periodontitis affects the severity of DR. This study aimed to explore the potential of P. gingivalis OMVs to contribute to the pathogenesis of DR and explore how it affect the retinal microvascular endothelium. The results demonstrated that P. gingivalis OMVs accelerated the blood-retinal barrier damage in DR mice. In vitro studies showed that the expression of inflammatory factors in human retinal microvascular endothelial cells (HRMECs) was increased after P. gingivalis OMVs stimulation, and the increased reactive oxygen species production, mitochondrial dysfunction, apoptosis, and altered endothelial permeability were observed in HRMECs under P. gingivalis OMVs stimulation. In addition, we found that protease-activated receptor-2 (PAR-2) regulated OMVs-induced TNF-α, MMP-9 mRNA expression, cell death, and endothelial permeability. Overall, we suggested that P. gingivalis OMVs induced mitochondria-related cell death of HRMECs and accelerated endothelial dysfunction, thus aggravating DR, in which PAR-2 plays a potential role. This study is the first research report to delineate the potential molecular mechanism of P. gingivalis OMVs on DR pathogenesis, which uniquely focused on elucidating the possible impact of periodontal pathogen derivatives on DR progression.